Managing Reading And Writing In English First Additional Language: A Case Of First Entering Education Students At The University Of Limpopo (Journal of Namibian Studies : History Politics Culture, 2023)
The paper critically engages on the causes of battling to read and write eloquently in English First Additional Language by the University of Limpopo’s first entering education students. The paper is both conceptual and empirical in nature. This is the qualitative case study design. Interviewing technique and document analysis were used to collect data from the thirty-six research participants represented by twenty-seven students, nine from each department within the School of Education and nine lecturers, three from each department in the school. Altogether, data were solicited from thirty-six research participants. Research findings reveal that firstly, battling to read and write by first entering education students stems from the existing gap between the primary, secondary and the tertiary education sectors. Secondly, that the closure of teacher training colleges of education aggravated the reading and writing challenge by learners. Thirdly, the previous years’ ongoing curricular changes at the primary and the secondary schooling sectors, consolidated the reading and writing predicament especially for the EFAL. Fourthly, insufficient culture of reading and writing by parents at the primary and secondary schooling sector, spilled over to the first entering students. Lastly, the generation of teachers at the primary and the secondary school level, who themselves pull hard to read and write eloquently, reinforce the said reading and writing problem. As part of the conclusion, the researchers recommend that the University’s School of Education needs to quickly adopt schools within the vicinity of the university to partner with them to alleviate this sorry state. In addition, there is an urgent need for the University’s School of Education to work in partnership with the primary and the secondary education institutions to lead the reading-for-joy campaign.